Illustrating the formation of metal nanoparticles with a growth concept based on colloidal stability1. Issue 30 (14th August 2015) - Wuithschick, M.; Witte, S.; Kettemann, F.; Rademann, K.; Polte, J.
<x xml:space="preserve">Abstract</x> The growth process of various colloidal metal nanoparticles is illustrated using a novel concept based on colloidal stability.